Cognitive Functional Therapy for persistent low back pain: A mixed methods feasibility study. - Newton, Christopher (2021)
Background Low back pain (LBP) is the most disabling and costly health condition globally, causing persistent pain and disability for more than ten million people in the United Kingdom (UK). Persistent LBP is characterised by a complex interplay of biopsychosocial factors that results in variable and fluctuating levels of pain and disability for each person. However, the contemporary management of persistent LBP has failed to integrate the multidimensional complexity of the disorder or target treatment towards individuals’ needs. A plethora of physical, behavioural, combined (physical and behavioural) and psychologically informed physiotherapy interventions have all resulted in modest reductions in pain and disability when compared to minimal treatment or care as usual, with no one type of intervention demonstrating superiority over another.